Impact of Social Media News Overload on Social Media News Avoidance and Filtering: Moderating Effect of Media Literacy - Tian, Qiuxia (Frontiers in Psychology, 2022)
In the present era of information technology, the reliance on seeking out news and relevant information has become very necessary in order to accomplish personal and organizational objectives. The review of the literature indicates that people tend to seek out news to enhance their current knowledge and awareness and to gain literacy. Therefore, the present study undertook an inquiry to investigate the impact of social media news overload on news avoidance and news filtering in the presence of mediating and moderating mechanisms of the need for news and media literacy. For this purpose, data were obtained from 358 Chinese social media users through the aid of survey forms. The data were analyzed through the use of the Smart-PLS software and a structural equation modeling (SEM) technique was applied to determine the validity of the proposed hypotheses. The results of the study suggested that social media news overload has a significant effect on news avoidance, the need for news, and news filtering behavior. It was also observed that the need for news had a significant relationship with news avoidance. Furthermore, it was seen that the need for news did not affect news filtering. In addition to this, it was also revealed that the need for news mediated the relationship between social media news overload and news avoidance whereas it did not mediate the relationship between social media news overload and news filtering. Lastly, it was observed that media literacy moderated the relationship between the need for news and news avoidance and it did not moderate the relationship between the need for news and news filtering behavior. This study made some important theoretical contributions by advancing the current literature in terms of present empirical evidence that points towards the significant relationship between social media news overload, news avoidance, and news filtering. Practically, this study contributed by emphasizing the need to encourage and train people to apply strategies to seek and find relevant news in a vast repository of information.